Combined endophytic inoculants enhance nickel phytoextraction from serpentine soil in the hyperaccumulator Noccaea caerulescens - Visioli, Giovanna; Vamerali, Teofilo; Mattarozzi, Monica; Dramis, Lucia; Sanangelantoni, Anna M. (Frontiers in Plant Science, 2015)
This study assesses the effects of specific bacterial endophytes on the phytoextraction capacity of the Ni-hyperaccumulator Noccaea caerulescens, spontaneously growing in a serpentine soil environment. Five metal-tolerant endophytes had already been selected for their high Ni tolerance (6 mM) and plant growth promoting ability. Here we demonstrate that individual bacterial inoculation is ineffective in enhancing Ni translocation and growth of N. caerulescens in serpentine soil, except for specific strains Ncr-1 and Ncr-8, belonging to the Arthrobacter and Microbacterium genera, which showed the highest IAA production and ACC-deaminase activity. Ncr-1 and Ncr-8 co-inoculation was even more efficient in promoting plant growth, soil Ni removal and translocation of Ni, together with that of Fe, Co and Cu. Bacteria of both strains densely colonised the root surfaces and intercellular spaces of leaf epidermal tissue. These two bacterial strains also turned out to stimulate root length, shoot biomass and Ni uptake in Arabidopsis thaliana grown in MS agar medium supplemented with Ni. It is concluded that adaptation of N. caerulescens in highly Ni-contaminated serpentine soil can be enhanced by an integrated community of bacterial endophytes rather than by single strains; of the former, Arthrobacter and Microbacterium may be useful candidates for future phytoremediation trials